2017
DOI: 10.3892/or.2017.5396
|View full text |Cite
|
Sign up to set email alerts
|

Calpain inhibitors ameliorate muscle wasting in a cachectic mouse model bearing CT26 colorectal adenocarcinoma

Abstract: Cancer-related cachexia involves increased protein breakdown through various proteolytic pathways, including the ubiquitin-proteasome pathway (UPP). We hypothesized that a calcium- and calpain-dependent pathway might play a crucial role during the proteolytic procedure, and that pathway interventions would ameliorate cancer cachexia in vivo. After being inoculated with CT26 adenocarcinoma cell culture subcutaneously, BALB/c mice developed cachexia in 12 days. They were then administered with different types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
7
0
3
Order By: Relevance
“…Furthermore, active calpain can promote muscle atrophy by inhibiting Akt activity [ 20 ] and activating FoxO3a, NF-κB, and ubiquitin E3 ligases [ 19 , 21 , 22 ]. A recent study [ 23 ] in our laboratory confirmed that an activated calpain system, as indicated by an increased calpain/calpastatin ratio, contributed to skeletal muscle wasting in cachexic tumor-bearing mice, and calpain inhibitors reversed this effect.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, active calpain can promote muscle atrophy by inhibiting Akt activity [ 20 ] and activating FoxO3a, NF-κB, and ubiquitin E3 ligases [ 19 , 21 , 22 ]. A recent study [ 23 ] in our laboratory confirmed that an activated calpain system, as indicated by an increased calpain/calpastatin ratio, contributed to skeletal muscle wasting in cachexic tumor-bearing mice, and calpain inhibitors reversed this effect.…”
Section: Introductionsupporting
confidence: 55%
“…We recently demonstrated that the presence of tumors increased calpain activity and decreased calpastatin expression in the skeletal muscle of cachexic mice [ 23 ]. Here, we performed western blot and RT-qPCR studies to investigate whether co-culture and AG/UnAG affected the expression of calpains and calpastatin in myotubes.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the literature report data supporting the involvement of Ca 2+ -dependent proteolysis in the pathogenesis of cancer-induced muscle wasting, protein hypercatabolism was not downregulated in preparations of isolated muscles obtained from tumor-bearing animals and incubated in the presence of calpain inhibitors [ 19 , 33 , 34 ]. More recently, both pharmacological and genetic approaches aimed at inhibiting the Ca 2+ -dependent proteolytic system were not able to prevent or delay cancer-induced muscle wasting [ 21 ], although contrasting results were reported in this regard [ 35 ].…”
Section: Protein and Amino Acid Metabolismmentioning
confidence: 99%
“…CT26 colorectal adenocarcinoma cell conditioned medium is often used to induce myotube atrophy to simulate CCMA in vitro (29,30). In addition, CT26 colorectal adenocarcinoma and BALB/c mice can be used to develop cancer cachectic tumor-bearing mice, as previously described (4). Thus, in the present study, CT26 cells were used to develop a cell co-culture model with myoblasts to simulate CCMA.…”
Section: Discussionmentioning
confidence: 96%